Wayang and Islamic Values: a Discourse - Mibtadin Mibtadin; Umi Masfiah (Javanologi: International Journal of Javanese Studies, 2023)
This article tries to see what the acculturation of wayang and Javanese culture is and what is the influence of wayang on Javanese people's behavior. This study uses qualitative research methods described descriptively. It is expected to be able to reveal the meaning that exists from the thoughts and actions of the object of research. For the delivery to be more open and natural, it is presented with a descriptive-analytical model. There are three steps of qualitative data processing, namely data reduction, data presentation, and drawing conclusions and verification. A puppet is a picture of human nature with all its behavior. In a moral sense, wayang is defined as a fairy tale about the story of a good character in the form of a hero fighting a bad character. Wayang is a portrait of life containing sanepa, piwulang, and pituduh. Wayang contains habits of life, and human behavior experienced from birth, life, and death, all of which are natural processes. Puppets became a medium of Islamic development by Sunan Kalijaga as a cultural da'wah that embeds Islam in the culture of society. Wayang by Sunan Kalijaga keeps it as a space for spirituality to encourage the spirit which is expected to encourage the Javanese people to be patient, trustful, and istiqomah (Consistent). Wayang is an effective da'wah (preaching) medium for the Javanese community in which it contains eastern aesthetic elements such as balance, unity, philosophy of life, ethics, and spirituality. Wayang is an emphasis on the balance of the microcosm and macrocosm, which has a balance between God, humans and other living beings, government and people, and symbols as the essence of being. Wayang is a way of life (mabda al-hayah) for the Javanese people to achieve the perfection of life seen where the view is centered on the concept of harmony. This concept is built on two main foundations: the need to avoid conflict and have an attitude of living in harmony. Both attitudes toward life must be carried out based on a respectful attitude that aims to create harmony in life. Puppets, in principle, seek to encourage the process of memayu hayuning pribadi (personal beautification), memayu hayuning keluarga (family beautification), memayu hayuning bangsa (national beautification), dan memayu hayuning bawana (global beautification).